EVALUASI MANAJEMEN PEMBELAJARAN DI MADRASAH - Putriani L Maliki; Alfian Erwinsyah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2020)
The purpose of this study is to describe the evaluation of learning management about learning management in Madrasah Tsanawiyah Negeri 1 Gorontalo City, to describe the inhibiting factors for the successful implementation of learning in Madrasah Tsanawiyah Negeri 1 Gorontalo City, and to describe the evaluation of learning in Madrasah Tsanawiyah Negeri 1 Gorontalo City. This research is categorized as a descriptive evaluative research with the approach used is a quantitative approach. Sources of data in this evaluation study came from: 1) documents that are administrative requirements of a program, 2) questionnaires (questionnaires) distributed to informants (students, principals, and teachers), and 3) interviews with the three informants. Data collection techniques used were questionnaire, observation, interview and documentation. While the data analysis technique used in this study is descriptive analysis of percentages. The results of this study indicate that overall learning management in Madrasah Tsanawiyah Negeri 1 Gorontalo City is classified as good, viewed from the aspect of learning planning, then followed by the implementation of learning until the evaluation of learning is classified successfully applied and beneficial to students in Madrasah Tsanawiyah Negeri 1 Gorontalo City especially in educators and grade VII and VIII students. Good criteria from the results of this study indicate that learning management is expected to be in accordance with the content standards in the curriculum in reality, namely in accordance with the stages of student development and conformity to the environment, as well as national development needs. Besides that learning management is planned, systematic and directed and is based on clear objectives. This can be seen from the planning / preparation of learning conducted by the teacher in the form of syllabus and lesson plans, implementation of learning that has been successful and good assessment / learning outcomes.